2022
DOI: 10.3389/frhs.2022.833214
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Maladaptive Anxious Avoidance in the Context of Implementation of Evidence-Based Interventions: A Commentary

Abstract: This paper posits that a clinician's own anxious reaction to delivering specific evidence-based interventions (EBIs) should be better accounted for within implementation science frameworks. A key next step for implementation science is to delineate the causal processes most likely to influence successful implementation of evidence-based interventions (EBIs). This is critical for being able to develop tailored implementation strategies that specifically target mechanisms by which implementation succeeds or fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
(100 reference statements)
1
4
0
Order By: Relevance
“…Relatedly, coaching parents to use time-out was emotionally evocative for several clinicians, and their colleague appeared to provide direct or indirect scaffolding to enhance their emotion regulation. This finding is in keeping with suggestions that clinicians’ anxiety relating to delivery of exposure-based tasks (e.g., within Cognitive Behavioural Therapy-based treatments for anxiety) ought to be better accounted for in implementation research and practice (Becker-Haimes et al, 2022 ; Deacon & Farrell, 2013 ).…”
Section: Discussionsupporting
confidence: 84%
“…Relatedly, coaching parents to use time-out was emotionally evocative for several clinicians, and their colleague appeared to provide direct or indirect scaffolding to enhance their emotion regulation. This finding is in keeping with suggestions that clinicians’ anxiety relating to delivery of exposure-based tasks (e.g., within Cognitive Behavioural Therapy-based treatments for anxiety) ought to be better accounted for in implementation research and practice (Becker-Haimes et al, 2022 ; Deacon & Farrell, 2013 ).…”
Section: Discussionsupporting
confidence: 84%
“…Therapists should potentially be trained specifically to manage their own anxious distress during treatment. In fact, developing implementation interventions that address therapist distress, such as helping therapists learn to manage their own anxious reactions, has been recommended [14,38]. A recent study found that 12 therapists who underwent experiential training reported improved attitudes towards exposure, one underused EBI [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therapist anxiety has been proposed as an additional factor impacting the uptake of EBIs [14,15]. In fact, preliminary research has suggested that higher rates of therapist anxiety, measured in one study as intolerance of uncertainty, are related to decreased use of evidence-based interventions, specifically exposure-based and behavioral experiments [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using insights from implementation science, or the scientific study of how to increase the use of EBPs in routine clinical settings to improve care quality ( 14 ), the past few decades have seen advances in efforts to understand the major barriers leading to the underutilization of Ex-CBT. Identified barriers range from concerns about the complex nature of the intervention itself ( 15 ) and poor marketing of Ex-CBT to practicing clinicians and families ( 16 ), negative beliefs and misconceptions about Ex-CBT held by clinicians ( 17 20 ), organizational constraints and intervention delivery challenges ( 21 , 22 ), and systemic barriers related to factors such as reimbursement rates and limited funding for specialized training ( 23 ). These implementation barriers also occur alongside historical underrepresentation of marginalized and minoritized individuals in clinical treatment trials and limited attention to ways of culturally tailoring treatments to increase engagement and effectiveness.…”
mentioning
confidence: 99%